Canadian Patent Agent Regulation Reform Pt. 2 – Governance, Self-Regulation and Canada’s Patent Professional Identity Crisis - Aoun, Wissam (2017)
Only registered Canadian patent agents may represent others before the Canadian Patent Office. To qualify as a registered Canadian patent agent, candidates must complete an apprenticeship followed by successfully passing the Canadian patent agent examination. This article analyzes the current regulatory framework for Canadian patent agents. Based on a theoretical, historical and international comparative analysis, this article demonstrates that the current Canadian regulatory model has lost sight of its purpose and is symptomatic of a greater crisis of legitimacy plaguing the Canadian patent agent profession. The article highlights the need for greater reform of the Canadian patent agent regulatory framework in order to better serve the intellectual property needs of the Canadian public. This article concludes with a series of comprehensive recommendations for reform of the current Canadian regulatory framework.
Keywords: Wissam Aoun